The Impact of ESG, Profitability, and Business Risk on Stock Returns: Evidence from the Indonesian Stock Market - Sarah Ayu Deva; Anak Agung Gde Satia Utama (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the impact of Environmental, Social, and Governance (ESG), profitability, and business risk on stock returns in the Indonesian stock market. The research utilizes panel regression analysis to assess the relationship between ESG scores, profitability, business risk, and stock returns of all publicly listed companies in Indonesia between 2020-2022. The results indicate that ESG does not significantly affect stock returns, which could be attributed to the prevalence of greenwashing in Indonesia. Profitability, shows a positive significant impact on stock returns, suggesting that more profitable companies tend to provide higher stock returns. Business risk negatively impacts stock returns, with companies facing higher risks showing lower returns due to greater price volatility. This study contributes to the theoretical understanding of the relationship between ESG, profitability, business risk, and stock returns in Indonesia. Practically, it offers valuable insights for investors to consider profitability and risk management over ESG claims when making investment decisions. The study is limited by its focus on Indonesian firms and the use of Bloomberg ESG scores, which may not fully capture the actual sustainability practices of companies.